EFEKTIFITAS LAYANAN INFORMASI DENGAN TEKNIK MODELING UNTUK MENUMBUHKAN MINAT BERWIRAUSAHA SISWA SMK - Ismail Sunny (Universitas PGRI Semarang, 2020)
This research is motivated by the lack of interest in entrepreneurshipstudent in SMK caused by students tend not been able to utilize and lessinterested in entrepreneurship in accordance with the skills they gain from eachdepartment. This research is quantitative research with pre-experimental designapproach one-group pretest-posttest design. The population used in this study isa class XI student of state SMK 7 Semarang the number of 108 students. Samplestaken as many as 27 students by using proportional random sampling technique.Based on the analysis of research data after receiving treatment in the form ofinformation services with modeling techniques to foster interest inentrepreneurship class XI student of state SMK 7 Semarang. Tcount at 12.20 andttable of 2,052 Due tcount (12.20)> t table (2.052) then this indicates that thesignificant t test values are significant at 5% level. Scores before treatment gainedan average of 68.67, while the average score after treatment reached 81.74 sothere is an increase of 13.07% So that can be concluded that the